EVALUASI PROMOSI DAN PELATIHAN HIGIENE DAN SANITASI PENJAMAH MAKANAN DI KANTIN SEKOLAH - Nirmala Tri Kartika (Jurnal Ilmu Kesehatan Masyarakat, 2017)
The Long Term Development Plan (2005-2024) focuses on health development towards a promotive and preventive health effort with one of its programs called Gerakan Masyarakat Sehat (Germas). This program is expected to increase everyone’s knowledge, awareness, willingness and ability to live healthy. One of the activities of Malang City Health Office to succeed the program is by training and Counseling of Hygiene and Sanitation for food handlers in School Canteen. for food handlers in School Canteen. The activity requires evaluation because the result of posttest score of participants is an average of 60. The results are influenced by participants who are not present continuously. This study aims to describe 6M component (material, money, machine, methode, man, and, measure). The research method used observation which used 6M component. In this activity there are 9 problems such as no material handout, budget adjusting with Malang city budget, fast discharging microphone batteries, some participants not present continuously, exposure only with lectures, not accompanied by training practices, inappropriate targets, and lack of organizing committee And low posttest results. 5 out of 9 such problems are given alternative problem solving such as arranging the rundown of the event, the speaker practice the material that he explained, briefing the coordinator of the puskesmas that will spread the invitation, and arrange the organizing committee which involves one field. Keywords: Training and Counseling, Food Handlers, Evaluation